Access and adequacy of antenatal care in a city in Brazil during two phases of the COVID-19 pandemic - Nicole Zazula Beatrici; Roxana Knobel; Mariana Schmidt Vieira; Iago Felipe Alexandrini; Alberto Trapani Júnior; Carla Betina Andreucci (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: To compare access and suitability of antenatal care between years 2020 and 2022 among postpartum individuals at a Hospital in Florianopolis, and evaluate factors associated with antenatal suitability. Methods: Observational, cross-sectional, and quantitative study carried out in 2022. Collected data were compared with the database of a previous similar study carried out in the same setting in 2020. Data were extracted from medical records and prenatal booklets, in addition to a face-to-face questionnaire. Adequacy was measured using the Carvalho and Novaes index and health access was qualitatively evaluated. Socio-demographic and antenatal variables were analyzed. A statistical significance level of 0.05 was considered. Open-ended questions were categorized for analysis. Results: 395 postpartum individuals were included. Antenatal care was adequate for 48.6% in 2020 and 69.1% in 2022. Among the barriers to access, 56% reported difficulty in scheduling appointments and/or exams and 23% complained of reduced healthcare staff due to strikes, COVID-19, among others. Adequate antenatal care was associated with being pregnant in 2022, being referred to high-risk units (PNAR), and not reporting difficulties in access. Also, it was associated with twice the chance of investigation for gestational diabetes (GDM) and syphilis. Conclusion: The 2022 post-vaccination period showed higher antenatal adequacy. The main difficulty for postpartum individuals was scheduling appointments and/or exams. Having antenatal care in 2022, no reports of difficulty in access, and follow-up at a high-risk unit were associated with antenatal adequacy.